Computer Program Development For Determenation Brooding Energy of Broiler Under Libya Conditions - Obaia, Abdel-Wahab Ramadan (Al-Mukhtar Journal of Sciences, 2011)
The present study was conducted in the AL-Beida, AL-Gabal AL-Akhdar region, , Libya and carried out during the period from September to May, 2008/2009, on broiler houses (open system). The objective of the study was to development of computer program for determenation brooding energy of broiler under region conditions. The computer program was written using VISUAL BASIC version 6.0, ventilation heat looses, building heat looses, sensible heat produced by bird were determined in this program. Data were collected from broiler open house in Al-Beida (cold weather), the program can predicted the maximum brooding energy of broiler house under different weather conditions. The following points were concluded based on the results of this study: The maximum brooding energy for the broiler house was found to be 3.32 W /bird, at minimum temperature (5 oC) in Al-Beida region. The minimum brooding energy for the broiler house was found to 0.55 W /bird, at maximim temperature (30 oC) in Al-Beida region. The average brooding energy for the broiler house was found to be 1.66 W /bird, at temperature (20 oC) in Al-Beida region.